Effect of low doses of herbicide paraquat on antioxidant defense in Drosophila - Sábová, Michala (Jihočeská univerzita, 2016)
Disruption of cell equilibrium between production of free radicals and antioxidant defence is named oxidative stress. The main component of antioxidant mechanism is activity of antioxidant enzymes, which include superoxide dismutase (SOD) and catalase. In this study we evaluated the effect of herbicide paraquat on response of SOD and catalase, their transcription level and locomotion activity in Drosophila melanogaster. We exposed the flies to a wide range of paraquat concentration. Our results revealed that transcript and enzymatic levels of both SOD and catalase have a similar biphasic dose response with the peaks at 2,5 ?M paraquat concentration, resembling hormetic effect. Then, males were more sensitive than females. However, females had an increased locomotion activity. We found that paraquat susceptibility is increased in males and mating flies. Therefore, this study supports hypothesis of stress sensitivity elevation as a physiological cost of reproduction.
Effect of low doses of herbicide paraquat on antioxidant defense in Drosophila
Keywords: superoxide dismutase; catalase; antioxidant mechanism; paraquat; Drosophila melanogaster; superoxide dismutase; catalase; antioxidant mechanism; paraquat; Drosophila melanogaster